Successful use of single‐pass albumin dialysis in the correction of severe hyperbilirubinemia in a case of acute hepatitis E. Issue 2 (25th July 2022) - Piscitani, Luca; Di Vito, Roberto; Tunno, Marilena; Bonomini, Mario
Abstract: Introduction: Acute liver failure (ALF) is a rare syndrome defined by the rapid loss of liver function in the absence of pre‐existing liver disease, which may be secondary to hepatitis A virus, hepatitis E virus (HEV), or to drugs in about 50% of cases. Extracorporeal albumin dialysis enables the elimination of albumin‐bound toxins that accumulate in liver failure. Methods: We report a case of ALF secondary to HEV associated with severe hyperbilirubinemia. Patient was treated with four consecutive sessions of single‐pass albumin dialysis (SPAD) carried out setting the following parameters: time: 300 min, Qb: 60 mL/min, Qd: 800–1000 mL/min, dialysate containing 4% albumin, citrate: 3–4 mmol/L. Result: SPAD documented good support of liver function. Bilirubin levels were reduced from 22 to 14 g/dL after four treatments. Pruritus was the first clinical sign of improvement. Conclusion: SPAD system can represent a safe and effective therapeutic option.